High throughput screening of valganciclovir in acidic mircoenvironments of polyester thin films - Schaller, Teilo (2015)
Ganciclovir and valganciclor are antiviral agents used for the treatment of cytomegalovirus retinitis. The conventional method for administering ganciclovir in cytomegalovirus retinitis patients is repeated intravitreal injections. In order to obviate the possible detrimental effects of repeated intraocular injections, to improve compliance and to eliminate systemic side-effects, we investigated the tuning of the ganciclovir pro-drug valganciclovir and the release from thin films of poly(lactic-co-glycolic acid) (PLGA), polycaprolactone (PCL), or mixtures of both, as a step towards prototyping periocular valganciclovir implants. To investigate the drug release, we established and evaluated a high throughput fluorescence-based quantification screening assay for the detection of valganciclovir. Our protocol allows quantifying as little as 20 ng of valganciclovir in 96-well polypropylene plates and a 50× faster analysis compared to traditional HPLC measurements. This improvement can hence be extrapolated to other polyester matrix thin film formulations using a high-throughput approach. The acidic microenvironment within the polyester matrix was found to protect valganciclovir from degradation with resultant increases in the half-life of the drug in the periocular implant to 100 days. Linear release profiles were obtained using the pure polyester polymers for 10 days and 60 days formulations; however, gross phase separations of PCL and acid-terminated PLGA prevented tuning within these timeframes due to the phase separation of the polymer, valganciclovir, or both.